A first account of tone in Myebon Sumtu Chin - Watkins, Justin (2024)
Sumtu Chin is spoken by some 20–30,000 people in four townships southeast of Sittwe in Arakan State, western Burma. Close analysis of tone systems in other southern Chin languages has proved difficult because the tones vary greatly between dialect; the data in this paper is from a single dialect of Sumtu, spoken in Myebon. Sumtu monosyllables may have lexical high or low tone. Grammaticalised morphemes may lose their underlying lexical tone and are assigned the polar opposite tone to the tone of the morpheme on the left. Functional morphemes may be lexically toneless, assigned a surface tone in a similar way. Restricted minor syllables preceding major syllables surface with the polar opposite tone to the major syllable to their right; verb-subject prefixes take the form of such minor syllables. The formation of the dual seems to flip the tone sequence of verbs